Report of the Signal Transduction Society meeting 2017: metabolism in health and disease - Schirmer, Bastian; Giehl, Klaudia; Hieke-Kubatzky, Katharina (International journal of molecular sciences, 2019)
The annual “Joint Meeting Signal Transduction - Receptors, Mediators and Genes” of the Signal Transduction Society (STS) aims to be an interdisciplinary forum for researchers who share a common interest in deciphering signal transduction pathways in normal or transformed cells, in health and disease, in humans and animal models, or in plants or bacteria. The special focus of the 21st annual Joint Meeting, which took place from 8–10 November 2017 in Weimar, was the topic “Metabolism in Health and Disease” and covered multiple aspects of this highly exciting and fast developing research field. Invited keynote speakers introduced the impact of metabolism on tumor immunology, immune cell signaling, and posttranslational modifications in three specific workshops to the audience. Various other aspects of signal transduction were intensively discussed in five additional workshops. Here, we give an overview of the various workshops and further aspects of the scientific program. Keywords: signal transduction; STS; conference report; metabolism; receptor signaling; infection and inflammation; cellular motility and cytoskeleton; translational cancer research; growth factors; cytokine